Criteria of Reducing the Amount of Compensation of Damage to Vehicles Considering the Decisions of the Constitutional Court and the Plenum of the Supreme Court of the Russian Federation - I. G. Novoseletskii; S. V. Fedotov (Теория и практика судебной экспертизы)
The article discusses the justification of considering wear and tear when estimating the amount of damage caused by vehicle breakage. The authors present the legal reasoning for the differentiated approach when deciding whether wear and tear should be considered and make some suggestions for its practical reflection in expert opinions